Kontradiksi, Preferensi Dan Rekonsiliasi (Al-Ta'arud Wa Al-Tarjih Wa Al-Jam') - Amri, M. Saeful Amri (Sekolah Tinggi Agama Islam Al-Hikmah 2, 2022)
Usul Fiqh is a scientific discipline that describes the methodology used by mujtahid priests in exploring and establishing a syar'i law that is sourced from the texts (AlQur'an or As-Sunnah). And in practice, in looking for the right legal basis to determine the law of a problem, it is often found that several arguments are contradictory to one another or known as Ta'arud al-adillah (contradiction). This study discusses the problem of how to find a way out if there is a contradiction in the propositions externally or textually. The ushuliyyin then formulated ways to solve this problem in several ways: (1) compromising conflicting arguments (al-jam'uwa altaufiq/reconciliation) or (2) conducting tarjih (selecting stronger arguments/preferences) through study Nasikh mansukh, or by canceling the contradictory arguments (tasaqut ad-dalilain).